Effect of Line Width and Thickness on Flexible Printed Electronic Circuit Electrical Performance - Mansor, Muhd Ridzuan (Journal of Mechanical Engineering and Technology (JMET), 2019)
Flexible and printable electronics is among the rapidly growing field in many applications. Their performances are affected by many factors such as the interaction between the conductive ink circuit and the type of flexible substrate used as the printed board. In this paper, the effect of the conductive ink circuitry line width and thickness to the flexible printed electronic (FPE) electrical performance is investigated. Commercial type carbon based conductive ink and polyethylene terephthalate (PET) flexible substrate were applied to formulate the FPE circuit, using screen printing technique and cured at room temperature, with varying circuitry line width (between 1.00 mm to 3.00 mm) and thickness (between 0.05 mm to 0.25 mm). The final resistivity for all samples were later tested using digital multimeter. Results for the experiments showed that the electrical resistivity of the FPE samples were alost inversely proportional to the dimension of the circuit thickness and width. The results obtained shall be used in the next project stage as benchmarking data to establish design guidelines related to circuitry geometrical parameters to obtain optimum FPE electrical performance in actual application.